Use of the BRANT-MERQS scoring table for the quality assessment of type 3 medication review in patients with rheumatoid arthritis and those with type 2 diabetes mellitus - Robberechts, Anneleen; Stas, Kaat; Puttemans, Margot; Poppe, Laura; Steurbaut, Stephane; De Meyer, Guido R. Y.; De Loof, Hans (Frontiers in Pharmacology, 2024)
A type 3 medication review (MR3) is a patient-centred medication service primarily provided by pharmacists and is presently employed routinely in several countries. In this process, pharmacists interview patients and collaborate with the treating physician to optimize the patient's pharmacotherapy, taking into account the patient's medication history and other medical data including laboratory values. The need to maintain the quality of such interventions during and after their initial implementation cannot be overstated.The objective of this study was to refine and assess a scoring table to evaluate the quality of MR3 conducted in Belgian community pharmacies.The comprehensive quality of MR3s was assessed by scoring its various components using a previously developed scoring table, called BRANT-MERQS, Brussels Antwerp Medication Review Quality Score. MR3s were analysed from an implementation study with patients suffering from rheumatoid arthritis (RA, subproject 1) and type 2 diabetes mellitus (T2DM, subproject 2). Additional information was obtained during a telephone call with a subset of participating pharmacists of subproject 1 who finalized their first MR3.In subproject 1, a total of 21 MR3s of patients with RA were examined. The assessment showed favourable scores for elements such as a well-organized medication schedule, treatment adherence, and the elaboration of specific interventions. However, certain other quality criteria posed challenges in the evaluation, for example the use of simple and understandable language. Pharmacists faced time constraints, and elderly general practitioners (GPs) displayed limited enthusiasm, which were notable barriers observed for this subproject.In the context of subproject 2 that investigated 41 MR3s in patients with T2DM, the quality criteria of interaction between pharmacist and GP and used sources and tools received high scores. However, there was still room for improvement, especially in areas such as accurate dosing, handling kidney function, QT prolongation, correctly associating laboratory values with relevant drugs and medical conditions, and optimisation of medication schedules for patients.This study demonstrated the feasibility of MR3 quality assessment through a scoring system. However, it also unveiled the tool's current imperfections and highlighted the ongoing need for refinement, something expected of a new service in an implementation phase.